COMPLEXO NÍQUEL(II)-BIS(1,10-FENANTROLINA) SUPORTADO EM ÓXIDO DE GRAFENO REDUZIDO PARA A ELETRO-OXIDAÇÃO DE ETANOL. - SANTOS, José Ribamar Nascimento dos (2017)
The electro-oxidation of ethanol was evaluated on a pyrolytic graphite electrode (PGE) chemically modified with the nickel(II)-bis(1,10-phenanthroline) complex (Ni(II)(Phen)2) supported on reduced graphene oxide (RGO) (rGO/Ni(II)(Phen)2/PGE). The Ni(II)(Phen)2 complex, reduced graphene oxide (rGO) and the rGO/Ni(II)(Phen)2 composite were prepared and characterized by the techniques of Spectroscopy in the UV-Vis, Fourier Transform Infrared Spectroscopy and Diffraction of X-rays. The electrocatalytic activity of the material was evaluated by cyclic voltammetry and chronoamperometry. In alkaline solution, the voltamograms obtained for rGO/Ni(II)(Phen)2/PGE showed the formation of well defined redox peaks associated with the Ni(II)/Ni(III) redox couple. The results showed that the RGO/Ni(II)(Phen)2 composite significantly increases the electrocatalytic activity for ethanol oxidation compared to the electrode modified only with the Ni(II)(Phen)2 complex. Using the Laviron theory, the charge transfer rate constant (ks) and the electron transfer coefficient (α) of the electrode reaction were calculated to be 0.56 s-1 and 0.61, respectively. A investigation of the electro-oxidation of ethanol was performed by evaluating the effect of different parameters such as potential scan rate, OH- concentration and alcohol concentration. The chronoamperometric experiments were used to determine the diffusion coefficient of ethanol (D = 4.7 Χ 10-6 cm2 s-1) and the catalytic rate constant (kcat = 1.26 Χ 107 cm3 mol-1 s-1). The results obtained in this study clearly indicate the viability of rGO/Ni(II)(Phen)2/PGE as an electrocatalyst for ethanol oxidation.